Monogamy Inequality in Terms of Higher Powers of a Correlation Measure: An Analysis - A. R. Usha Devi; . Sudha; P. J. Geetha (New Insights into Physical Science Vol. 13, 2021)
We begin with the basic notions of limited shareability of quantum correlations, the so-called monogamous nature of quantum states and outline how this feature is manifested through a monogamy inequality. Not all measures of quantum correlations are suitable for bringing out the restricted shareability of correlations in a quantum state. While measures of bipartite correlations such as concurrence, quantum discord do not satisfy monogamy inequality for all categories of correlated quantum states, their second powers are found to do. There has also been a proposition that all multiparty quantum states can be made monogamous by considering positive integral powers of any quantum correlation measure (Ann. Phys. 348, 297 (2014)). We focus on this proposition and analyze whether satisfying monogamy inequality in terms of higher powers of a correlation measure implies limited shareability of correlations.